Aconitate decarboxylase 1 mediates the acute airway inflammatory response to environmental exposures - Schwab, Aaron D.; Nelson, Amy J.; Gleason, Angela M.; Schanze, Oliver W.; Wyatt, Todd A.; Shinde, Dhananjay D.; Xiao, Peng; Thomas, Vinai C.; Guda, Chittibabu; Bailey, Kristina L.; Kielian, Tammy; Thiele, Geoffrey M.; et al. (Frontiers in Immunology, 2024)
Background: Environmental lipopolysaccharide (LPS) and microbial component-enriched organic dusts cause significant lung disease. These environmental exposures induce the recruitment and activation of distinct lung monocyte/macrophage subpopulations involved in disease pathogenesis. Aconitate decarboxylase 1 (Acod1) was one of the most upregulated genes following LPS (vs. saline) exposure of murine whole lungs with transcriptomic profiling of sorted lung monocyte/macrophage subpopulations also highlighting its significance. Given monocyte/macrophage activation can be tightly linked to metabolism, the objective of these studies was to determine the role of the immunometabolic regulator ACOD1 in environmental exposure-induced lung inflammation.Methods: Wild-type (WT) mice were intratracheally (I.T.) instilled with 10 µg LPS or saline. Whole lungs were profiled using bulk RNA sequencing or sorted to isolate monocyte/macrophage subpopulations. Sorted subpopulations were then characterized transcriptomically using a NanoString innate immunity multiplex array 48 hours post-exposure. Next, WT and Acod1 -/-mice were instilled with LPS, 25% organic dust extract (ODE), or saline, whereupon serum, bronchoalveolar lavage fluid (BALF), and lung tissues were collected. BALF metabolites of the tricarboxylic acid (TCA) cycle were quantified by mass-spectrometry. Cytokines/chemokines and tissue remodeling mediators were quantitated by ELISA. Lung immune cells were characterized by flow cytometry. Whole body plethysmography was performed 3 hours post-LPS with WT and Acod1 -/-mice.Results: Acod1 -/-mice treated with LPS demonstrated decreased BALF levels of itaconate, TCA cycle reprogramming, decreased BALF neutrophils, increased lung CD4 + T cells, decreased BALF and lung levels of TNF-a, and decreased BALF CXCL1 compared to WT animals. In comparison, Acod1 -/-mice treated with ODE demonstrated decreased serum pentraxin-2, BALF levels of itaconate, lung total cell, neutrophil, monocyte, and B cell infiltrates with decreased BALF levels of TNF-a, IL-6, and decreased lung CXCL1 vs. WT animals. Mediators of tissue remodeling (TIMP1, MMP8, MMP9) were also decreased in the LPS-exposed Acod1 -/-mice, with MMP-9 also reduced in ODE-exposed Acod1 -/-mice. Lung function assessments demonstrated a blunted response to LPSinduced airway hyper-responsiveness in Acod1 -/-animals.Acod1 is robustly upregulated in the lungs following LPS-exposure and encodes a key immunometabolic regulator. ACOD1 mediates the pro-inflammatory response to acute inhaled, environmental LPS and organic dust exposure-induced lung inflammation.